Comprehensive planning and future prospects for development in the Latakia region - سعود ربى (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Comprehensive planning research and future prospects for development in the Lattakia region deals with the elements of development in the Lattakia region, as there are essential elements in this region for the success of the development process from an important geographic marine location that constitutes a transportation node between three continents, in addition to important natural characteristics that enhance the chances of success for development , in terms of a moderate climate, distinctive and diverse topographical features, the availability of fertile agricultural areas and the availability of the necessary water resources and basic services for the development process, all with a human and labor force enjoying distinct demographic, economic and social characteristics, which help create worthy development opportunities for the region, but All of these elements faced basic challenges as a result of the lack of combination of these factors and the absence of planning for most of their components, and it was necessary to plan in order to fully coordinate the various economic and social activities of the parts of the same region, using the development methodology driven by the considerations of local communities, through carefully drawn directions and sound planning with the aim of establishing A comprehensive and successful development in the region, working to develop the lives of the population, and raise their standard of living. Comprehensive planning research and future prospects for development in the Lattakia region deals with the elements of development in the Lattakia region, as there are essential elements in this region for the success of the development process from an important geographic marine location that constitutes a transportation node between three continents, in addition to important natural characteristics that enhance the chances of success for development , in terms of a moderate climate, distinctive and diverse topographical features, the availability of fertile agricultural areas and the availability of the necessary water resources and basic services for the development process, all with a human and labor force enjoying distinct demographic, economic and social characteristics, which help create worthy development opportunities for the region, but All of these elements faced basic challenges as a result of the lack of combination of these factors and the absence of planning for most of their components, and it was necessary to plan in order to fully coordinate the various economic and social activities of the parts of the same region, using the development methodology driven by the considerations of local communities, through carefully drawn directions and sound planning with the aim of establishing A comprehensive and successful development in the region, working to develop the lives of the population, and raise their standard of living .